Control of sensitivity in vortex-type magnetic tunnel junction magnetometer sensors by the pinned layer geometry. (12th May 2022) - Endo, Motoki; Al-Mahdawi, Muftah; Oogane, Mikihiko; Ando, Yasuo
Abstract: The tuning of sensitivity and dynamic range in linear magnetic sensors is required in various applications. We demonstrate the control and design of the sensitivity in magnetic tunnel junction (MTJ) sensors with a vortex-type sensing layer. In this work, we develop sensor MTJs with NiFe sensing layers having a vortex magnetic configuration. We demonstrate that by varying the pinned layer size, the sensitivity to magnetic field is tuned linearly. We obtain a high magnetoresistance ratio of 140%, and we demonstrate a controllable sensitivity from 0.85% Oe −1 to 4.43% Oe −1, while keeping the vortex layer fixed in size. We compare our experimental results with micromagnetic simulations. We find that the linear displacement of vortex core by an applied field makes the design of vortex sensors simple. The control of the pinned layer geometry is an effective method to increase the sensitivity, without affecting the vortex state of the sensing layer. Furthermore, we propose that the location of the pinned layer can be used to realize more sensing functionalities from a single sensor.